Reporting Verbs in L1 and L2 English Novice Academic Writing - Markéta Malá; Gabriela Brůhová; Kateřina Vašků (ELOPE, 2022)
The paper contributes to the research on academic attribution by exploring syntactic-semantic patterns of English reporting verbs used by three types of academic writers, namely L2 novice (with Czech as their L1), L1 novice and L1 expert academic writers. It investigates the impact which both the EFL and EAP challenge has on the use of these verbs by L2 novice academic writers. Our approach combines contrastive analysis and learner corpus research, focusing on academic writing in English in the discipline of economics. The results suggest that although similarities among the groups prevail, Czech novice academic writers tend to resort to patterns associated with informal, conversational rather than academic style. Pedagogical implications of the findings could include raising students’ awareness of the practice of appropriate academic reporting as one of the skills needed for them to accommodate themselves to the conventions of English as the academic lingua franca.